Técnicas para execução de experimentos sob ambiente protegido para a cultura da abobrinha italiana - Feijó, Sandra (2005)
In order to determinate technicals to execution trials in protected environments for italian pumpkin was accomplished an experiment, from 18/08/2003 to 07/12/2003, in the area of the Department of Fitotecnia UFSM, in plastic greenhouse, with four rows and each row consisted of twenty-four plants. A total of twenty-seven harvests were made, evaluating fruit weight with length ≥15cm. The sample soil was sampled before accomplishment the experiment; one sample point is equal to four sub sample. The Smith heterogeneity index was estimated using SMITH s method (1938) and optimum plot size using method modified maximum curvature (MEIER & LESSMAN, 1971). Estimate, for how long productive period of italian pumpkin, in plastic greenhouse, must be evaluated aiming to estimate the experimental error and the difference among four intervals of harvest, was the aim in order to first paper. The harvest and evaluation of the initial half of the productive period of Italian pumpkin in plastic greenhouse was sufficient to estimate the experimental error, using six plants by plot, to evaluate different intervals of harvest. Because of high experimental error, the evaluation of the Italian pumpkin production during all the productive period is not sufficient to differentiate four treatments of intervals of harvest. The aim the second paper, was evaluate the chemicals characteristics of the soil heterogeneity index under environmental protect and determinate sample size. The values the Smith heterogeneity index were considerate small. The optimum plot size was equal to one basic unit, in other words, one sample point. The sample size estimated was ten sample points for the half width of the confidence interval of 20%, to 5% of error probability. The third paper, aimed evaluate the Smith heterogeneity index in order to different intervals of the harvest of fruits in different levels of the accumulate harvests of italian pumpkin in greenhouse, estimate the optimum plot size and determinate the least significant differences within treatments with variation in the size plot and number of replications. The Smith heterogeneity index is smaller and the use of smaller plots with larger number of replications benefit the experimental precision. The optimum plot size in order to yield italian pumpkin varying between one and seven plants, promoted appropriate evaluation of the yield italian pumpkin in the different studied treatments. Plots with three plants and six replications is better in order conduction the experiments, with least significant differences within treatments (average percentage) in 75,94%.